Ancestry, Goodness, and the Relationship with Christianity as Ecodomical Aspects of Decolonization in Indigenous African Religions - Simuţ, Corneliu C. (Journal for the Study of Religion & Ideologies, 2017)
This paper is an attempt to identify common factors which constitute the foundation of decolonization in indigenous African religions. Since such aspects need to be essentially constructive in order to effectively and positively replace Colonial ideas, this particular search for common ground concerning decolonization in indigenous African religions is going to be pursued through the concept of ecodomy, seen as constructive process. When applied to decolonization with this postulated positivity, ecodomy coagulates three distinct aspects of indigenous African religions into a common reality. These three aspects are ancestry, goodness, and the relationship with Christianity; they can function therefore as common denominator for various attempts to provide indigenous African religions with specific methodology in dealing with decolonization. This article is going to investigate four such methodologies which can confer positivity as well as an ecodomic, constructive character to decolonization efforts throughout the spectrum of indigenous African religions as they are reflected in the writings of John Mbiti, Isiaka P. Laleye, Jakob K. Olupona, and Israel Kamudzandu, all intellectuals of different geographical origin, religious backgrounds, university training, and personal convictions. With Mbiti promoting the superiority of Christianity, Laleye accepting it as irrelevant, Olupona preferring to deal without it, and Kamudzandu seeing it as essential, decolonizing efforts in indigenous African religions have at least four different methodologies which all aim at providing African communities with positive and ecodomic, essentially constructive ways to move forward beyond Colonial intellectual paradigms by making sure that peace and goodness are secured for everybody, African or not.
free
Keywords: Africa – Church history; Africa – Intellectual life; Africa – Religion; Ancestors – Religious aspects – African religion; Christianity and African religions; Colonialism and neocolonialism; Decolonization; Kamudzandu; Israel; Laléyê; Issiaka Prosper; Mbiti; John S; 1931-; Olupona; Jacob Obafemi Kehinde; Philosophy; African